2004
DOI: 10.1038/sj.tpj.6500255
|View full text |Cite|
|
Sign up to set email alerts
|

Linkage analysis of smoking initiation and quantity in Dutch sibling pairs

Abstract: The heritability of smoking initiation (SI) and number of cigarettes smoked (NC) was determined in 3657 Dutch twin pairs. For SI a heritability of 36% was found and for NC of 51%. Both SI and NC were also significantly influenced by environmental factors shared by family members. The etiological factors that influence these traits partly overlap. Linkage analyses were performed on data of 536 DZ twins and siblings from 192 families, forming 592 sibling pairs. Results suggested QTLs on chromosome 6 (LOD ¼ 3.05)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
54
3
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 38 publications
7
54
3
1
Order By: Relevance
“…Although the prevalence of smoking has decreased significantly in many countries, particularly among men, the number of highly dependent smokers has not declined correspondingly. 28 In previous linkage analyses, smoking behavior as a phenotype has been defined in several different ways: average 7,15 or maximum 29,30 number of cigarettes smoked per day, ever smoking, 31 habitual smoking 17,18 and total number of cigarette packs per day for 1 year. 14 Similarly, ND can be defined in various ways, the most commonly used definitions being based on the DSM-IV 32 and the FTND.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the prevalence of smoking has decreased significantly in many countries, particularly among men, the number of highly dependent smokers has not declined correspondingly. 28 In previous linkage analyses, smoking behavior as a phenotype has been defined in several different ways: average 7,15 or maximum 29,30 number of cigarettes smoked per day, ever smoking, 31 habitual smoking 17,18 and total number of cigarette packs per day for 1 year. 14 Similarly, ND can be defined in various ways, the most commonly used definitions being based on the DSM-IV 32 and the FTND.…”
Section: Discussionmentioning
confidence: 99%
“…Twin and family studies have suggested a high heritability (56-75%) for ND; [3][4][5][6][7] clearly, social, psychological and other environmental factors as well as comorbidities, such as alcohol use and depression, contribute as well. 8,9 Several genome-wide scans have been performed suggesting loci linked to smoking behavior and ND.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 Loci identified with other smoking phenotypes also contain some biologically interesting candidates, such as a region on chromosome 5q located near the dopamine receptor (D 1 ) gene, which has been reported in several studies. 32,40,41 Regions on chromosomes 6, 9 and 11 26,32,33,[40][41][42][43][44][45][46] are also promising as several studies have replicated the linkage and these regions contain some potential biologically relevant candidate genes (Table 1).…”
Section: Genome-wide Linkage Studiesmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][20] This may be due, at least in part, to the broadness of this phenotype which encompasses those who have only tried cigarettes once to regular heavy smokers. Once smoking is initiated, the heritability for persistence to regular smoking has been estimated at 28-84%, 12,[15][16][17][19][20][21] for number of cigarettes smoked at 45-86% [21][22][23][24][25][26] and for diagnosed ND at 31-75%. 19,21,27 A genetic influence on nicotine withdrawal symptoms and smoking cessation has also been identified with heritability estimated at 26-48 and 50-58%, respectively.…”
Section: Introductionmentioning
confidence: 99%